Negative ion diaphragm and preparation method thereof

By adding modified negative ion nanopowders to the substrate layer of the negative ion separator, a three-layer structure negative ion separator is prepared, which solves the problems of ozone pollution and high usage costs in the prior art, and achieves a more efficient air purification effect.

CN119552591AActive Publication Date: 2025-03-04HEYUAN XUAN LANG OPTO-ELECTRONIC TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411820199.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-04
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

In the existing negative ion air purification technology, the negative ion generator will produce secondary pollutants such as ozone, and the negative ion adsorption material is costly and has low purification efficiency.

Method used

By adding modified negative ion nanopowders to the substrate layer, a three-layer structure negative ion separator of negative ion functional layer, adhesive layer and substrate layer is prepared to maximize the loading of negative ion ore nanopowder and improve air purification efficiency.

Benefits of technology

Without affecting the membrane's breathability, water absorption and transmittance, the production capacity of negative ions and air purification efficiency are significantly improved, and the use cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552591A_ABST
    Figure CN119552591A_ABST
Patent Text Reader

Abstract

The invention relates to a negative ion diaphragm and a preparation method thereof, and the preparation method comprises the following steps: firstly preparing a base material layer added with negative ion ore nano powder, then coating one surface of the base material layer with a negative ion ore nano functional layer, and coating the other surface of the base material layer with an adhesive layer added with negative ion ore nano powder. According to the preparation method, the negative ion functional layer, the negative ion base material layer and the negative ion adhesive layer all contain the negative ion ore nano-powder, and the negative ion membrane with the negative ion functional layer, the negative ion base material layer and the negative ion adhesive layer all contain the negative ion ore nano-powder. More negative ion ore nanometer powder capable of generating negative oxygen ions is loaded to the maximum extent, and the air purification efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional membrane preparation, and in particular relates to a negative ion membrane and a preparation method thereof. Background Art

[0002] With the development of industry and the increase in population, the problem of air pollution is becoming increasingly serious. Harmful substances in the air, such as particulate matter, sulfur dioxide, nitrogen oxides, carbon monoxide, etc., pose a great threat to human health. Therefore, air purification technology has become an important research direction in the field of environmental protection. At present, the World Health Organization has set the negative oxygen ion content of fresh air to 1000-1500 per cubic centimeter. Negative ion technology has received widespread attention because it can effectively remove harmful substances in the air and has the advantages of purifying the air, sterilizing and disinfecting, and regulating human physiological functions.

[0003] Existing negative ion air purification technologies mainly include negative ion generators and negative ion adsorption materials. Negative ion generators ionize water molecules in the air to generate negative ions through corona discharge and other methods; these negative ions can combine with harmful substances in the air to form harmless substances, thereby achieving the purpose of purifying the air; but negative ion generators will produce secondary pollutants such as ozone during operation, posing a potential threat to human health. Negative ion adsorption materials adsorb harmful substances in the air through physical or chemical methods and fix them on the surface of the material, thereby achieving the purpose of purifying the air; but negative ion adsorption materials are easily saturated during use and need to be replaced frequently, increasing the cost of use. Therefore, a negative ion membrane is proposed to solve the problems of secondary pollutants such as ozone and high cost of use when using negative ion generators or negative ion adsorption materials.

[0004] The existing Chinese patent CN111721052A discloses a method for preparing a glass heat-insulating film for removing formaldehyde by negative ions, which comprises applying a heat-insulating coating on the surface of a transparent film substrate; then applying a layer of negative ion mixture material on the heat-insulating coating, placing it in an environment with a temperature of 105°C, and curing it for 125 seconds to form a negative ion coating, wherein the negative ion mixture material is composed of tourmaline negative ion powder, modified brucite powder, titanium dioxide, silane coupling agent, and polyurethane adhesive; and then applying a layer of protective film on the negative ion coating. The negative ion removal formaldehyde glass film prepared by this preparation method produces limited negative ions per unit time, and has low purification efficiency; and it only uses tourmaline negative ion powder as the ore for producing negative ions, and cannot produce negative ions in other scenarios that do not meet the conditions for tourmaline to produce negative ions, which limits its available purification scenarios and cannot meet people's high-quality demand for air purification in an increasingly severe air pollution environment. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a negative ion membrane.

[0006] The method for preparing a negative ion membrane of the present invention comprises the following steps:

[0007] Adding modified negative ion nano powder to the raw material of the substrate to prepare a negative ion-based material slurry, and applying the negative ion-based material slurry to prepare a negative ion substrate layer;

[0008] Coating a layer of negative ion functional slurry with modified negative ion nano powder on one side of the negative ion substrate layer to form a negative ion functional layer;

[0009] Coating a layer of adhesive added with modified negative ion nanopowder on the other side of the negative ion substrate layer to form a negative ion adhesive layer;

[0010] A release film is attached to the negative ion adhesive layer to prepare a negative ion separator of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer / release layer.

[0011] Compared with the prior art, the negative ion membrane preparation method provided by the present invention comprises the following steps: first preparing a substrate layer added with negative ion mineral nanopowder, then coating a negative ion mineral nanofunctional layer on one side of the substrate layer, and coating an adhesive layer added with negative ion mineral nanopowder on the other side of the substrate layer, so as to prepare a negative ion membrane in which the three layers of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer all contain negative ion mineral nanopowder. The preparation method can load more negative ion mineral nanopowder that can generate negative oxygen ions to the maximum extent on the inherent area of ​​the negative ion membrane without affecting the air permeability, water absorption and transmittance of the membrane, thereby improving the air purification efficiency.

[0012] Furthermore, the preparation of the negative ion substrate layer is as follows:

[0013] SA1: adding 10% to 20% by mass of modified anion nano powder to the raw material of the base material to prepare anion-based material slurry;

[0014] SA2 sequentially stirs, vacuum degasses, and allows the negative ion base material slurry to stand for defoaming, and then prepares the negative ion base material layer by coating.

[0015] Furthermore, the substrate is TPU or TAC or SRF.

[0016] Furthermore, the preparation of the negative ion functional slurry is as follows:

[0017] SC1 adds 10% to 20% by mass of modified anion nano powder to PU resin to prepare a resin mixture;

[0018] SC2 adds 200% isopropyl alcohol solvent to the resin mixture to make functional slurry;

[0019] SC3 stirs the functional slurry, vacuum degasses it, and allows it to stand for defoaming to obtain a negative ion functional slurry.

[0020] Furthermore, the preparation of the adhesive added with modified anion nanopowder is as follows:

[0021] SD1 adds 20% to 30% by mass of modified anion nano powder to the adhesive to prepare an adhesive mixture;

[0022] SD2 adds 50% of ester solvent to the adhesive mixture to prepare adhesive slurry;

[0023] SD3 stirs the adhesive slurry to obtain an adhesive with modified anion nanopowder added.

[0024] Furthermore, the preparation method of the modified anion nanopowder is as follows:

[0025] S1 converts the spheroidal graphite with the ability to generate negative ions into negative ion ore nano powder;

[0026] S2 adds a modifier to the negative ion ore nano powder, and obtains modified negative ion nano powder after mixing, stirring, high temperature heating, and natural cooling.

[0027] Furthermore, the ore having the ability to generate negative ions is one or more of Tianshou Stone, Liuhuan Stone, and Seagull Stone.

[0028] Furthermore, the particle size of the negative ion mineral nanopowder includes three particle size grades, namely 0.002mm-0.005mm, 0.006mm-0.01mm, and 0.011-0.05mm, and the maximum particle size thereof does not exceed the thickness of the substrate.

[0029] Furthermore, the modifier is one or more of oxides or hydroxides of cerium and titanium.

[0030] At the same time, the present invention also provides a negative ion membrane, which has a negative ion functional layer / negative ion substrate layer / negative ion adhesive layer / release layer structure prepared by any of the above preparation methods.

[0031] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A schematic diagram of a preparation process according to an embodiment of the present invention;

[0033] Figure 2Schematic diagram of the negative ion membrane prepared by the present invention. DETAILED DESCRIPTION

[0034] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0035] In order to solve the problem that the negative ions produced per unit time and per unit area by the negative ion membrane prepared by the existing preparation method are limited and the purification efficiency is low, the present invention studies a preparation method of a negative ion membrane. The preparation method first prepares a substrate layer added with negative ion mineral nanopowder, then coats a negative ion mineral nanofunctional layer on one side of the substrate layer, and coats an adhesive layer added with negative ion mineral nanopowder on the other side of the substrate layer, so as to prepare a negative ion membrane in which the three layers of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer all contain negative ion mineral nanopowder. The preparation method loads more negative ion mineral nanopowder that can produce negative oxygen ions to the maximum extent on the negative ion membrane of the inherent area without affecting the air permeability, water absorption and transmittance of the membrane, thereby improving the purification efficiency of the air.

[0036] See also Figure 1 and Figure 2 The preparation method of the negative ion membrane of the present application is described in detail below, which includes the following steps.

[0037] (I) Preparation of modified anion nanopowder

[0038] S1 converts the spheroidal graphite with the ability to generate negative ions into negative ion ore nano powder.

[0039] The spherical ink equipment is a three-roll grinding equipment and a high-speed ball mill.

[0040] The ore capable of generating negative ions is one or more of Tianshou stone, Liuhuan stone and Haiou stone. A combination of multiple ores with different negative ion generating mechanisms is preferred, so that the modified negative ion nano powder can ensure that at least one ore can generate negative ions in different application scenarios.

[0041] The particle size of the negative ion ore nano powder includes three particle size grades, namely 0.002mm-0.005mm, 0.006mm-0.01mm, and 0.011-0.05mm, and the maximum particle size does not exceed the thickness of the substrate.

[0042] The particle size grade of each ore in the multiple ore combination is the same. The mass ratio of each ore in the multiple ore combination is the same.

[0043] S2 adds a modifier to the negative ion ore nano powder, and obtains modified negative ion nano powder after mixing, stirring, high temperature heating, and natural cooling.

[0044] The modifier is one or more of cerium and titanium oxides or hydroxides. The modifier can catalytically increase the rate at which the negative ion ore nanopowder generates negative ions.

[0045] The high temperature heating has a heating temperature of 550° C. to 650° C., preferably 600° C.; the heating time is 4 hours to 6 hours, preferably 5 hours.

[0046] The content of the modifier accounts for 3% to 6% of the mass percentage of the negative ion ore nano powder.

[0047] (II) Preparation of negative ion membrane

[0048] S3: adding modified negative ion nano powder to the raw material of the substrate to prepare a negative ion-based material slurry, and applying the negative ion-based material slurry to prepare a negative ion substrate layer.

[0049] The specific steps include:

[0050] SA1 adds 10% to 20% by mass of the modified anion nano powder prepared in step S2 to the raw material of the substrate to prepare an anion-based material slurry;

[0051] SA2 sequentially stirs, vacuum degasses, and allows the negative ion base material slurry to stand for defoaming, and then prepares the negative ion base material layer by coating.

[0052] The substrate is TPU, TAC, SRF. TPU is preferably used as the substrate, and the raw materials of TPU are polymer materials such as polyols and polyisocyanates. When TPU is used as the substrate, there will be gaps between the ore particles of the same particle size, and TPU itself has good air permeability. Air enters the interior of TPU and electrolyzes the ore particles inside TPU to generate and release negative ions.

[0053] The standing time is 20 to 30 minutes.

[0054] The thickness of the negative ion substrate layer is 0.05 mm to 0.2 mm.

[0055] S4: coating a layer of negative ion functional slurry with modified negative ion nano powder added on one side of the negative ion substrate layer to form a negative ion functional layer.

[0056] The negative ion functional slurry is prepared by the following method:

[0057] SC1 adds 10% to 20% by mass of the modified anion nano powder prepared in step S2 to the PU resin to prepare a resin mixture;

[0058] SC2: adding 200% by mass of isopropyl alcohol solvent to the resin mixture to prepare a functional slurry;

[0059] SC3 stirs the functional slurry, vacuum degasses it, and allows it to stand for defoaming to obtain a negative ion functional slurry.

[0060] The thickness of the PU resin adhesive coating is 0.005mm to 0.01mm, and it only sticks to the bottom part of the original ore, so that the original ore powder on the film surface can be exposed to the air as much as possible, so that the original ore powder can have 100% unobstructed contact with the air, can produce the maximum amount of negative ions by electrolysis for a long time, and can be completely released into the air.

[0061] The thickness of the negative ion functional layer is 0.02 mm to 0.05 mm.

[0062] S5: coating a layer of adhesive added with modified negative ion nanopowder on the other side of the negative ion substrate layer to form a negative ion adhesive layer, thereby preparing a negative ion membrane of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer.

[0063] The adhesive added with modified anion nanopowder is prepared by the following method:

[0064] SD1: adding 20% ​​to 30% by mass of the modified anion nanopowder prepared in step S2 to the adhesive to prepare an adhesive mixture;

[0065] SD2: Add 50% by weight of ester solvent to the adhesive mixture to prepare adhesive slurry;

[0066] SD3 stirs the adhesive slurry to obtain an adhesive added with modified anion nanopowder.

[0067] The adhesive is a low-VOC, high-temperature resistant adhesive.

[0068] The thickness of the negative ion adhesive layer is 0.015mm-0.5mm.

[0069] S6: after baking the negative ion membrane of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer prepared in step S5, a release film is attached to the negative ion adhesive layer to prepare a negative ion membrane of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer / release layer.

[0070] The release film is a PET film.

[0071] The thickness of the release film is 0.025 mm-0.2 mm.

[0072] The technical scheme and technical effects of the present invention are further described below in conjunction with embodiments and comparative examples.

[0073] It should be noted that the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] Example 1

[0075] In this embodiment, the negative ion membrane is prepared according to the following method.

[0076] S1: 1000g of Tianshou stone, 1000g of Liuhuan stone and 1000g of Haiou stone are respectively spheroidized into 0.002mm-0.05mm ore nano powders by three-roll grinding equipment and high-speed ball mill; Tianshou stone nano powders, Liuhuan stone nano powders and Haiou stone nano powders of the same particle size level of 0.002mm-0.005mm are screened and mixed together in a mass ratio of 1:1:1 to form negative ion ore nano powders.

[0077] S2: adding 3% of cerium oxide to the negative ion ore nano powder, mixing and stirring, heating at 600° C. for 5 hours, and naturally cooling, to obtain modified negative ion nano powder.

[0078] S3 prepares negative ion-based material slurry with a mass ratio of TPU raw material: modified negative ion nanopowder = 80%:20%; the negative ion-based material slurry is stirred, vacuum degassed, and allowed to stand for 20 minutes to defoam, and then a negative ion substrate layer with a thickness of 0.05 mm is prepared by coating.

[0079] S4 prepares functional slurry with a mass ratio of PU resin: modified negative ion nanopowder: isopropyl alcohol solvent = 80%: 20%: 200%; the functional slurry is stirred, vacuum degassed, and allowed to stand for 20 minutes to defoam, and then a negative ion functional layer with a thickness of 0.02 mm is prepared on the negative ion substrate layer by coating.

[0080] S5 prepares an adhesive mixture with a mass ratio of adhesive: modified negative ion nanopowder: lipid solvent = 70%: 30%: 50%; a layer of adhesive mixture with a thickness of 0.02 mm is coated on the side of the negative ion substrate layer not coated with the negative ion functional layer to form a negative ion adhesive layer, and a negative ion membrane of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer is prepared.

[0081] S6: After baking the negative ion membrane of the negative ion functional layer / negative ion substrate layer / negative ion adhesive layer prepared in step S5 at 105° C. for 3 min, the release film is attached to the negative ion adhesive layer to prepare a negative ion separator.

[0082] Example 2

[0083] In this embodiment, the negative ion membrane is prepared according to the following method.

[0084] S1: Grind 1000g of Tianshou Stone, 1000g of Liuhuan Stone and 1000g of Haiou Stone into 0.002mm-0.05mm ore nano powders by three-roll grinding equipment and high-speed ball mill respectively; select Tianshou Stone nano powders, Liuhuan Stone nano powders and Haiou Stone nano powders of the same particle size level of 0.006mm-0.01mm and mix them together in a mass ratio of 1:1:1 to form negative ion ore nano powders.

[0085] S2: adding 5% titanium oxide to the negative ion ore nano powder, mixing and stirring, heating at 600° C. for 5 hours, and naturally cooling, to obtain modified negative ion nano powder.

[0086] S3 prepares negative ion-based material slurry with a mass ratio of TPU raw material: modified negative ion nanopowder = 85%:15%; the negative ion-based material slurry is stirred, vacuum degassed, and allowed to stand for 20 minutes to defoam, and then a negative ion substrate layer with a thickness of 0.05 mm is prepared by coating.

[0087] S4 prepares functional slurry with a mass ratio of PU resin: modified negative ion nanopowder: isopropyl alcohol solvent = 85%: 15%: 200%; the functional slurry is stirred, vacuum degassed, and allowed to stand for 20 minutes to defoam, and then a negative ion functional layer with a thickness of 0.03 mm is prepared on the negative ion substrate layer by coating.

[0088] S5 prepares an adhesive mixture with a mass ratio of adhesive: modified negative ion nanopowder: lipid solvent = 75%: 25%: 50%; a layer of adhesive mixture with a thickness of 0.03 mm is coated on the side of the negative ion substrate layer not coated with the negative ion functional layer to form a negative ion adhesive layer, and a negative ion membrane of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer is prepared.

[0089] S6: After baking the negative ion membrane of the negative ion functional layer / negative ion substrate layer / negative ion adhesive layer prepared in step S5 at 105° C. for 3 min, the release film is attached to the negative ion adhesive layer to prepare a negative ion separator.

[0090] Example 3

[0091] In this embodiment, the negative ion membrane is prepared according to the following method.

[0092] S1: 1000g of Tianshou stone, 1000g of Liuhuan stone and 1000g of Haiou stone are respectively spheroidized into 0.002mm-0.05mm ore nano powders by three-roll grinding equipment and high-speed ball mill; Tianshou stone nano powders, Liuhuan stone nano powders and Haiou stone nano powders of the same particle size level of 0.011-0.05mm are screened and mixed together in a mass ratio of 1:1:1 to form negative ion ore nano powders.

[0093] S2: adding 6% cerium hydroxide to the negative ion ore nano powder, mixing and stirring, heating at 600° C. for 5 hours, and naturally cooling, to obtain modified negative ion nano powder.

[0094] S3 prepares negative ion-based material slurry with a mass ratio of TPU raw material: modified negative ion nanopowder = 90%:10%; the negative ion-based material slurry is stirred, vacuum degassed, and allowed to stand for 20 minutes to defoam, and then a negative ion substrate layer with a thickness of 0.05 mm is prepared by coating.

[0095] S4 prepares functional slurry with a mass ratio of PU resin: modified negative ion nanopowder: isopropyl alcohol solvent = 90%: 10%: 200%; the functional slurry is stirred, vacuum degassed, and allowed to stand for 20 minutes to defoam, and then a negative ion functional layer with a thickness of 0.05 mm is prepared on the negative ion substrate layer by coating.

[0096] S5 prepares an adhesive mixture with a mass ratio of adhesive: modified negative ion nanopowder: lipid solvent = 80%: 20%: 50%; a layer of adhesive mixture with a thickness of 0.05 mm is coated on the side of the negative ion substrate layer not coated with the negative ion functional layer to form a negative ion adhesive layer, and a negative ion membrane of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer is prepared.

[0097] S6: After baking the negative ion membrane of the negative ion functional layer / negative ion substrate layer / negative ion adhesive layer prepared in step S5 at 105° C. for 3 min, the release film is attached to the negative ion adhesive layer to prepare a negative ion separator.

[0098] Comparative Example 1

[0099] S1` 1000g of tourmaline is spheroidized into 0.002mm-0.05mm tourmaline nano powder by three-roll grinding equipment and high-speed ball mill, and the particle size grade of 0.011-0.05mm is screened to form negative ion ore nano powder.

[0100] S3' Prepare a TPU substrate layer with a thickness of 0.05 mm by coating.

[0101] S4 prepares functional slurry with a mass ratio of PU resin: tourmaline nanopowder: isopropyl alcohol solvent = 90%: 10%: 200%; the functional slurry is stirred, vacuum degassed, and allowed to stand for 20 minutes to defoam, and then a negative ion functional layer with a thickness of 0.05 mm is prepared on the TPU substrate layer by coating.

[0102] S5` An adhesive mixture is prepared with a mass ratio of adhesive: lipid solvent = 100%:50%; a layer of the adhesive mixture with a thickness of 0.05 mm is coated on the side of the TPU substrate layer not coated with the negative ion functional layer to form an adhesive layer, and a negative ion membrane of tourmaline functional layer / substrate layer / adhesive layer is prepared.

[0103] S6: After baking the negative ion membrane of the negative ion functional layer / substrate layer / adhesive layer prepared in step S5 at 105° C. for 3 min, the release film is attached to the negative ion adhesive layer to prepare a negative ion separator.

[0104] Comparative Example 2

[0105] S1: 1000g of Tianshou stone, 1000g of Liuhuan stone and 1000g of Haiou stone are respectively spheroidized into 0.002mm-0.05mm ore nano powders by three-roll grinding equipment and high-speed ball mill; Tianshou stone nano powders, Liuhuan stone nano powders and Haiou stone nano powders of the same particle size level of 0.011-0.05mm are screened and mixed together in a mass ratio of 1:1:1 to form negative ion ore nano powders.

[0106] S2: adding 6% cerium hydroxide to the negative ion ore nano powder, mixing and stirring, heating at 600° C. for 5 hours, and naturally cooling, to obtain modified negative ion nano powder.

[0107] S3' Prepare a TPU substrate layer with a thickness of 0.05 mm by coating.

[0108] S4 prepares functional slurry with a mass ratio of PU resin: modified negative ion nanopowder: isopropyl alcohol solvent = 90%: 10%: 200%; the functional slurry is stirred, vacuum degassed, and allowed to stand for 20 minutes to defoam, and then a negative ion functional layer with a thickness of 0.05 mm is prepared on the TPU substrate layer by coating.

[0109] S5` An adhesive mixture is prepared with a mass ratio of adhesive: lipid solvent = 100%:50%; a layer of the adhesive mixture with a thickness of 0.05 mm is coated on the side of the TPU substrate layer not coated with the negative ion functional layer to form an adhesive layer, and a negative ion membrane of negative ion functional layer / substrate layer / adhesive layer is prepared.

[0110] S6: After baking the negative ion membrane of the negative ion functional layer / substrate layer / adhesive layer prepared in step S5 at 105° C. for 3 min, the release film is attached to the negative ion adhesive layer to prepare a negative ion separator.

[0111] Results Test Analysis

[0112] The negative ion membranes prepared in Examples 1 to 3 and the composite coating prepared in the comparative example were tested and analyzed for negative ion and formaldehyde concentrations. The test results are shown in Table 1.

[0113] Test environment conditions: temperature 15℃~35℃, relative humidity 40%~60%.

[0114] Test equipment and test conditions:

[0115] 1. Negative ions

[0116] Test equipment: negative ion tester, standard ventilation box with the size of 500mm*500mm*500mm;

[0117] Test environment: Indoors where the formaldehyde concentration exceeds 1 mg / m3;

[0118] Test method:

[0119] 1) Prepare the above-mentioned standard air permeable box, place the negative ion tester in the middle of the bottom of the box and turn it on to test the background negative ion content. After waiting for 1 hour, record the background negative ion content;

[0120] 2) The negative ion membrane prepared by the method described in the present invention is attached to one side of the inner wall of the air-permeable standard box, and the negative ion tester is placed in the middle of the bottom of the box and turned on to test the negative ion content of the sample. After waiting for 1 hour, the negative ion content of the sample of the negative ion membrane is recorded.

[0121] 2. Formaldehyde concentration

[0122] Test equipment: air monitor, standard ventilation box with the size of 500mm*500mm*500mm;

[0123] Test environment: Indoors where the formaldehyde concentration exceeds 1 mg / m3;

[0124] Test method:

[0125] 1) Prepare the above-mentioned standard air permeable box, place the air monitor in the middle of the bottom of the box and turn it on to test the background formaldehyde concentration. After waiting for 1 hour, record the background formaldehyde concentration;

[0126] 2) The negative ion membrane prepared by the method of the present invention is attached to one side of the inner wall of a breathable standard box, an air monitor is placed in the middle of the bottom of the box and turned on to test the formaldehyde concentration of the sample, and after waiting for 1 hour, the formaldehyde concentration of the sample of the negative ion membrane is recorded.

[0127] Table 1

[0128]

[0129] Analyze the performance characterization test results in Table 1.

[0130] The above data show that the negative ion generation capacity and formaldehyde purification capacity of the modified negative ion nanopowder prepared by the present invention are better than those of the mineral nanopowders sold on the market. The negative ion membrane prepared by the present invention has a more excellent negative ion generation capacity and formaldehyde purification capacity based on the addition of mineral powders to both the substrate and the adhesive layer, and can load more negative ion mineral nanopowders that can generate negative oxygen ions to the maximum extent without affecting the air permeability, water absorption and transmittance of the membrane, thereby improving the air purification efficiency.

[0131] The present invention is not limited to the above-mentioned embodiments. If various changes or modifications to the present invention do not depart from the spirit and scope of the present invention, and if these changes and modifications fall within the scope of the claims and equivalent technologies of the present invention, the present invention is also intended to include these changes and modifications.

Claims

1. A method for preparing a negative ion membrane, characterized in that: The steps include: Adding modified negative ion nano powder to the raw material of the substrate to prepare a negative ion-based material slurry, and applying the negative ion-based material slurry to prepare a negative ion substrate layer; Coating a layer of negative ion functional slurry with modified negative ion nano powder on one side of the negative ion substrate layer to form a negative ion functional layer; Coating a layer of adhesive added with modified negative ion nanopowder on the other side of the negative ion substrate layer to form a negative ion adhesive layer; A release film is attached to the negative ion adhesive layer to prepare a negative ion separator of negative ion functional layer / negative ion substrate layer / negative ion adhesive layer / release layer.

2. The preparation method according to claim 1, characterized in that: The preparation of the negative ion substrate layer is as follows: SA1: adding 10% to 20% by mass of modified anion nano powder to the raw material of the base material to prepare anion-based material slurry; SA2 sequentially stirs, vacuum degasses, and allows the negative ion base material slurry to stand for defoaming, and then prepares the negative ion base material layer by coating.

3. The preparation method according to claim 2, characterized in that: The substrate is TPU or TAC or SRF.

4. The preparation method according to claim 1, characterized in that: The preparation of the negative ion functional slurry is as follows: SC1 adds 10% to 20% by mass of modified anion nano powder to PU resin to prepare a resin mixture; SC2 adds 200% isopropyl alcohol solvent to the resin mixture to make functional slurry; SC3 stirs the functional slurry, vacuum degasses it, and allows it to stand for defoaming to obtain a negative ion functional slurry.

5. The preparation method according to claim 1, characterized in that: The preparation of the adhesive added with modified anion nano powder is as follows: SD1 adds 20% to 30% by mass of modified anion nano powder to the adhesive to prepare an adhesive mixture; SD2 adds 50% of ester solvent to the adhesive mixture to prepare adhesive slurry; SD3 stirs the adhesive slurry to obtain an adhesive added with modified anion nanopowder.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method of the modified anion nano powder is as follows: S1 converts the spheroidal graphite with the ability to generate negative ions into negative ion ore nano powder; S2 adds a modifier to the negative ion ore nanopowder, and obtains modified negative ion nanopowder after mixing, stirring, high temperature heating, and natural cooling.

7. The preparation method according to claim 6, characterized in that: The ore having the ability to generate negative ions is one or more of Tianshou stone, Liuhuan stone and Haiou stone.

8. The preparation method according to claim 7, characterized in that: The particle size of the negative ion ore nano powder includes three particle size grades, namely 0.002mm-0.005mm, 0.006mm-0.01mm, and 0.011-0.05mm, and the maximum particle size does not exceed the thickness of the substrate.

9. The preparation method according to claim 7 or 8, characterized in that: The modifier is one or more of oxides or hydroxides of cerium and titanium.

10. A negative ion membrane, characterized in that: The invention comprises a negative ion functional layer / negative ion substrate layer / negative ion adhesive layer / release layer structure prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Ultrasonic defrosting and deicing freshness preservation constant humidity refrigerator

    CN111721052A

  • Negative ion induced powder, composition containing same and coating partner

    CN110305520A

  • Method for preparing medical energy sheet

    CN110368595A

  • Ultrafine powder additive capable of inducing negative air ions and preparation process thereof

    CN118787771A

  • Negative ion generating decorative sheet material

    JP2003053904A